THE IMPACT OF USING ELSA APPLICATION TO IMPROVE STUDENTS PRONUNCIATION PRACTICE - M. Maarif Ramdhani; Rima Rahmaniah (Indonesian EFL Journal, 2025)
Pronunciation is essential for students to speak clearly and accurately. However, achieving correct pronunciation is a major challenge for many students, who find it difficult to pronounce words correctly. The aim of this study was to identify the impact of using ELSA application toward students' pronunciation practice. This study used a quantitative methotd with a descriptive approach and using survey to collect data, from the active students of Universitas Muhammadiyah Mataram. The primary data collection for this study was conducted by distributing questionnaires to 62 respondents. The questionnaire contains items that are validated and reliable, ensuring that each item accurately reflects the dimension it measures. The validity test showed that the calculated r value for each question item was greater than the r table and the reliability test showed that the Cronbach's alpha value was 0.954 for the use of the ELSA application and 0.976 for the improvement of pronunciation practice. The findings from this study corroborate the strong internal consistency of the study instrument. The study utilized a descriptive approach to describe the data distribution of both variables, by showing a mean score of 124.60 on the use of the ELSA application that the majority of respondents actively utilized the ELSA application. Conversely, the improvement of pronunciation practice showed a mean score of 79.55 that substantial improvement in pronunciation practice.